Reproductive cycle and fecundity of Potimirim glabra (Kingsley, 1954) (Caridea, Atyidae) from a littoral stream - Hoffmann, Patrícia [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP] (Taylor & Francis, 2010)
The reproductive cycle of Potimirim glabra, especially the female size at sexual maturity, reproductive period and fecundity, was studied at two sites of one of the northern littoral streams in the state of São Paulo, Brazil. Prawns were collected monthly for one year. The minmum size at sexual maturity was estimated from the smallest ovigerous female (cephalothorax length = CL), and the reproductive period was determined monthly by examining the relative frequency of ovigerous females. Size comparisons between sampling sites was carried out using the Mann-Whitney u test. The relationship between environmental factors and reproductive aspects was verified using the Spearman's rank correlation. At Site 1, the collected ovigerous females had a CL mean size of 4.24±0.36 mm (n=481); at Site 2, ovigerous females (n=391) had a CL mean size of 5.48±0.49 mm. The reproductive pattern in Camburi is seasonal, with the highest frequency of ovigerous females in February. The frequency of ovigerous females was positively correlated to organic matter content in the substratum, rainfall and temperature. Increased percentage organic matter may indicate greater food availability whereas higher rainfall increases the velocity of the current, thereby aiding the larvae, which depend on brackish water to complete their development, to reach the estuarine region. The temperature acts on the speed of larval development. At Site 1, the mean fecundity obtained was 202±72.31 eggs (90 females; CL from 2.7 to 4.7mm PL), whereas at Site 2, it was 433.3±120.7 eggs (46 females; CL from 4.0 to 5.5mm PL). © 2010 Balaban.
Keywords: Brazil; Freshwater prawn; Reproduction; Tropical stream